Effect of Sal (Shorea robusta) seed meal on growth and carcass quality in broiler (Bangladesh Journal of Animal Science, 2017)
This study was conducted to investigate the effect of dietary sal (Shorea robusta) seed meal (SSM) on growth performance, carcass characteristics and economic feasibility in broilers. Two hundred day-old, straight-run (Cobb-500) broiler chicks were randomly allocated to five dietary treatments for 42 days feeding trial (40 birds each). Dietary treatments were designed according to SSM supplementation levels, namely control diet (0% SSM), diets containing 10 and 15% of un-boiled SSM (USSM), and diets containing 15 and 20% of boiled SSM (BSSM). At the end of feeding trial, 20 birds (2birds per replication) were subjected for determining the meat yield parameters. Overall weight gain of control and 0% BSSM 2group was higher (p